2017
DOI: 10.18045/zbefri.2017.2.427
|View full text |Cite
|
Sign up to set email alerts
|

The Tourism and Travel Industry and Its Effect on the Great Recession: A Multilevel Survival Analysis

Abstract: Does a country with a heavy dependence on a tourism economy have a tendency to succumb to more risk in a recession

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Richards (2005) emphasizes the need to differentiate cultural tourism from a conceptual and operational point of view regard to new tourism trends. Numerous authors suggested some other development forms according to their analysis of visitation effects of destinations (Šergo et al, 2017, Poudyal et al, 2013, Eugenio-Martin and Campos-Soria, 2014 and also importance of collaborative economy (Dredge, 2017) and quantitative and qualitative approaches in tourism (Dwyer et al, 2017) as a priority for understanding new tourism issues and approaches.…”
Section: New Tourist Approach -Theoretical Backgroundmentioning
confidence: 99%
“…Richards (2005) emphasizes the need to differentiate cultural tourism from a conceptual and operational point of view regard to new tourism trends. Numerous authors suggested some other development forms according to their analysis of visitation effects of destinations (Šergo et al, 2017, Poudyal et al, 2013, Eugenio-Martin and Campos-Soria, 2014 and also importance of collaborative economy (Dredge, 2017) and quantitative and qualitative approaches in tourism (Dwyer et al, 2017) as a priority for understanding new tourism issues and approaches.…”
Section: New Tourist Approach -Theoretical Backgroundmentioning
confidence: 99%